2018
DOI: 10.1093/trstmh/try099
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of a lateral flow immunoassay (LFI) in serum samples for diagnosis of melioidosis

Abstract: BackgroundCulture is the gold standard for the diagnosis of melioidosis, an infection caused by Burkholderia pseudomallei. Here we evaluate a lateral flow immunoassay (LFI) to detect B. pseudomallei capsular polysaccharide (CPS) in serum samples.MethodsPatients with culture from any clinical specimen positive for B. pseudomallei were selected as cases. Patients who were blood culture positive for Staphylococcus aureus, Escherichia coli or Klebsiella pneumoniae as well as those who were malaria or dengue polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 8 publications
4
21
0
Order By: Relevance
“…We previously demonstrated that the CPS-LFI had limited sensitivity (31.3%) but high specificity (98.8%) for diagnosing melioidosis among patients presenting with community-acquired infections or sepsis in northeast Thailand when stored serum were tested [ 15 ]. Here, we evaluated combinations of the CPS-LFI and Hcp1- or OPS-ELISA for diagnosis of melioidosis.…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that the CPS-LFI had limited sensitivity (31.3%) but high specificity (98.8%) for diagnosing melioidosis among patients presenting with community-acquired infections or sepsis in northeast Thailand when stored serum were tested [ 15 ]. Here, we evaluated combinations of the CPS-LFI and Hcp1- or OPS-ELISA for diagnosis of melioidosis.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, rapid diagnostic lateral flow immunoassays (LFI) have been developed for use in laboratory settings where molecular and ELISA methods are generally not available. The Active Melioidosis Detect LFI (InBios International Inc., USA) detects soluble B. pseudomallei capsular polysaccharide and has high sensitivity and specificity (98.7% and 97.2%, respectively) when tested against B. pseudomallei isolates (17) but performs poorly when used with urine and blood samples (17)(18)(19). A recent study in Laos demonstrated that this LFI had high specificity when testing turbid blood culture bottles (100%), pus (100%), sputum (100%), sterile fluid (100%), and urine (90.7%).…”
Section: Discussionmentioning
confidence: 99%
“…Latex agglutination using beads conjugated with B. pseudomallei-specific monoclonal antibodies could identify bacterial colonies isolated from clinical samples at a high sensitivity (99.1%) with a reduced time to report (16). An immunochromatography assay using capsule polysaccharide-specific monoclonal antibody to detect bacterial components had reasonable specificity (93.6%) but low sensitivity (85.7%) (17,18), particularly when applied to blood samples (31.3% sensitivity) (19). PCR detection of the T3SS gene cluster provides Ͼ80% sensitivity (20), but direct detection of bacteria in clinical specimens is problematic, as pathogen concentrations are generally very low (21).…”
mentioning
confidence: 99%
“…The AMD-LFA, which detects B. pseudomallei 6-deoxyheptan capsular polysaccharide antigen, has been specifically developed for resource-poor, melioidosis-endemic settings where B. pseudomallei culture is frequently not available. 25 It has been evaluated on blood culture broths in Cambodia and Laos 26 and directly on clinical samples in Australia, 27 Laos, 28 , 29 Thailand 30 and India. 31 Shaw et al 31 demonstrated an overall sensitivity of 86% (CI 75 to 93) and specificity of 94% (CI 88 to 97) with a positive predictive value of 86% (CI 76 to 92) compared with culture on multiple types of specimens.…”
Section: Discussionmentioning
confidence: 99%